Speech Perception Benefits of Internet Versus Conventional Telephony for Hearing-Impaired Individuals - Mantokoudis, Georgios; Dubach, Patrick; Pfiffner, Flurin; Kompis, Martin; Caversaccio, Marco; Senn, Pascal (JMIR Publications, 2012)
BackgroundTelephone communication is a challenge for many hearing-impaired individuals. One important technical reason for this difficulty is the restricted frequency range (0.3-3.4 kHz) of conventional landline telephones. Internet telephony (voice over Internet protocol [VoIP]) is transmitted with a larger frequency range (0.1-8 kHz) and therefore includes more frequencies relevant to speech perception. According to a recently published, laboratory-based study, the theoretical advantage of ideal VoIP conditions over conventional telephone quality has translated into improved speech perception by hearing-impaired individuals. However, the speech perception benefits of nonideal VoIP network conditions, which may occur in daily life, have not been explored. VoIP use cannot be recommended to hearing-impaired individuals before its potential under more realistic conditions has been examined. ObjectiveTo compare realistic VoIP network conditions, under which digital data packets may be lost, with ideal conventional telephone quality with respect to their impact on speech perception by hearing-impaired individuals. MethodsWe assessed speech perception using standardized test material presented under simulated VoIP conditions with increasing digital data packet loss (from 0% to 20%) and compared with simulated ideal conventional telephone quality. We monaurally tested 10 adult users of cochlear implants, 10 adult users of hearing aids, and 10 normal-hearing adults in the free sound field, both in quiet and with background noise. ResultsAcross all participant groups, mean speech perception scores using VoIP with 0%, 5%, and 10% packet loss were 15.2% (range 0%-53%), 10.6% (4%-46%), and 8.8% (7%-33%) higher, respectively, than with ideal conventional telephone quality. Speech perception did not differ between VoIP with 20% packet loss and conventional telephone quality. The maximum benefits were observed under ideal VoIP conditions without packet loss and were 36% (P = .001) for cochlear implant users, 18% (P = .002) for hearing aid users, and 53% (P = .001) for normal-hearing adults. With a packet loss of 10%, the maximum benefits were 30% (P = .002) for cochlear implant users, 6% (P = .38) for hearing aid users, and 33% (P = .002) for normal-hearing adults. ConclusionsVoIP offers a speech perception benefit over conventional telephone quality, even when mild or moderate packet loss scenarios are created in the laboratory. VoIP, therefore, has the potential to significantly improve telecommunication abilities for the large community of hearing-impaired individuals.